Low cost and easy rice husk modification to efficiently enhance ammonium and nitrate adsorption - Lada Mathurasa; Seelawut Damrongsiri (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose This research aimed to study the adsorption of ammonium and nitrate by simply modifying the surface of the rice husk using slow pyrolysis and surfactants modification. Methods Rice husk biochar was prepared by slowly pyrolyzing at 500 °C, 2 h. The rice husk and its biochar were modified by cetyltrimethylammonium bromide or sodium dodecylbenzenesulfonate. FTIR, BET and zeta potential measurements were used to characterize the obtained adsorbents. Results Slow pyrolysis increased the specific surface area and decreased the surface charge of rice husk while surfactant clogged the pore but could change the charge of a surface. Adsorption of both ammonium and nitrate on rice husk, its biochar, and their modification with surfactants fitted Freundlich and Langmuir isotherms, indicating heterogeneity in adsorption. Slow pyrolysis gave the highest ammonium removal with maximum adsorption capacity of 44 mgN/g and it was a physical process. The cetyltrimethylammonium bromide modification gave a significant nitrate removal on both rice husk and its biochar with maximum adsorption of 278 and 213 mgN/g, respectively, which is higher than a commercial adsorbent. Conclusions These two modification techniques gave great adsorption enhancement with cost-effectiveness as compared to other reviewed methods which could use as a nitrogen-rich fertilizer and fertilizer retainment in crop production.